Cortex Integrity Relevance in Muscle Synergies in Severe Chronic Stroke - García-Cossio, Eliana; Broetz, Doris; Birbaumer, Niels; Ramos-Murguialday, Ander (Frontiers in Human Neuroscience, 2014)
Background: Recent experimental evidence has indicated that the motor system coordinates muscle activations through a linear combination of muscle synergies that are specified at the spinal or brainstem networks level. After stroke upper limb impairment is characterized by abnormal patterns of muscle activations or synergies. Objective: This study aimed at characterizing the muscle synergies in severely affected chronic stroke patients. Furthermore, the influence of integrity of the sensorimotor cortex on synergy modularity and its relation with motor impairment was evaluated. Methods: Surface electromyography from 33 severely impaired chronic stroke patients was recorded during six bilateral movements. Muscle synergies were extracted and synergy patterns were correlated with motor impairment scales. Results: Muscle synergies extracted revealed different physiological patterns dependent on the preservation of the sensorimotor cortex. Patients without intact sensorimotor cortex showed a high preservation of muscle synergies. On the contrary, patients with intact sensorimotor cortex showed poorer muscle synergies preservation and an increase in new generated synergies. Furthermore, the preservation of muscle synergies correlated positively with hand functionality in patients with intact sensorimotor cortex and subcortical lesions only. Conclusions: Our results indicate that severely paralyzed chronic stroke patient with intact sensorimotor cortex might sculpt new synergy patterns as a response to maladaptive compensatory strategies.